2019
DOI: 10.17221/93/2018-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fungal degradation on physicochemical properties of exploited stumps of oriental beech over a 25-year felling period and the obtained Kraft pulp properties

Abstract: Oriental beech (Fagus orientalis Lipsky) is the most important and valuable industrial wood species in the Hyrcanian forests in the north of Iran mainly used for furniture, veneer, composite, and papermaking industries. The present research was conducted in 2014 aimed at investigating the physicochemical changes of the felled oriental beech stumps over a 2–25 year period, and likewise the feasibility of using the given stumps as an alternative resource for wood pulp production. To do so, the effects of in-situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…20,21,24,[27][28][29] The existing publications evidence that water absorption of repeatedly recycled wood plastic composites (WPCs) depends on many variables such as interface quality, chemical composition, fiber length and distribution, density, and wood extractives. [30][31][32][33] The results confirm that globally recycling process reduces water absorption rates, thus boosting dimensional stability in WPCs. This is mainly due to better fiber dispersion, higher density, fewer and smaller voids, better fiber/polymer interfacial adhesion, and enhanced hydrophobicity in reprocessed polypropylene and polyethylene WPCs.…”
Section: Introductionmentioning
confidence: 62%
“…20,21,24,[27][28][29] The existing publications evidence that water absorption of repeatedly recycled wood plastic composites (WPCs) depends on many variables such as interface quality, chemical composition, fiber length and distribution, density, and wood extractives. [30][31][32][33] The results confirm that globally recycling process reduces water absorption rates, thus boosting dimensional stability in WPCs. This is mainly due to better fiber dispersion, higher density, fewer and smaller voids, better fiber/polymer interfacial adhesion, and enhanced hydrophobicity in reprocessed polypropylene and polyethylene WPCs.…”
Section: Introductionmentioning
confidence: 62%
“…A similar study was also reported by Rees, where the primary infection starts when oil palm roots in contact with fungal mycelia, and penetration occurred through the unwounded root. Invasion of root cortex and parenchyma resulted in the development of holes in all cell wall layers and rapid progression of colonization of the lower stem [27] increasing wood porosity and easier penetration [23]. Degradation of cell wall resulted in the formation of cavities within cell wall [27], separation of the parenchymatous cells and fibers in the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderma boninense is a white-rot fungus due to its ability to enzymatically degrade lignin, a component of oil palm wood. This enzymatic degradation causes a decrease in wood strength during the initial stages of decay [13,22,23]. White-rot fungi play a crucial role in the short-term conversion and degradation of wood polysaccharides [13,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other synthetic biodegradable polymers such as PVA and polyamide have also been reinforced with natural fibres and nanofibres. The results indicated that the addition of such reinforcements could improve the mechanical strength and moduli (due to the stiffening effect of natural fibres) and thermal stability of the resulting biocomposites, which the latter can be attributed to the reduced polymer chain mobility brought about by nanofibre inclusion (Kakroodi et al 2014;Naghdi et al 2015;Oliver-Ortega et al 2016;Yousefi et al 2017;Rahmati et al 2019).…”
Section: Synthetic Biopolymer Compositesmentioning
confidence: 99%